2017
DOI: 10.15557/jou.2017.0026
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of juvenile spondyloarthritis. Part II: Ultrasonography and magnetic resonance imaging

Abstract: Juvenile spondyloarthropathies are mainly manifested by symptoms of peripheral arthritis and enthesitis. Early involvement of sacroiliac joints and spine is exceptionally rare in children; this usually happens in adulthood. Conventional radiographs visualize late inflammatory lesions. Early diagnosis is possible with the use of ultrasonography and magnetic resonance imaging. The first part of the article presented classifications and radiographic presentation of juvenile spondyloarthropathies. This part discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Furthermore, a recent retrospective study in a group of 34 children with IBD who underwent magnetic resonance enterography (MRE) for gastrointestinal disease evaluation have shown that ve had radiological signs of SI in ammation at MRE, although no patient complained of musculoskeletal symptoms, nor had pathological ndings at articular examination (37). This is somewhat in line with the observation that MRI is more sensitive in the assessment of in ammatory and destructive changes in JIA and jSpA than physical examination, radiographs or ultrasound (38). With this in mind, our study for the rst time gives some clue that the concomitant in ammation of the gut and sacroiliac joints can be present early in the course of SpA.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, a recent retrospective study in a group of 34 children with IBD who underwent magnetic resonance enterography (MRE) for gastrointestinal disease evaluation have shown that ve had radiological signs of SI in ammation at MRE, although no patient complained of musculoskeletal symptoms, nor had pathological ndings at articular examination (37). This is somewhat in line with the observation that MRI is more sensitive in the assessment of in ammatory and destructive changes in JIA and jSpA than physical examination, radiographs or ultrasound (38). With this in mind, our study for the rst time gives some clue that the concomitant in ammation of the gut and sacroiliac joints can be present early in the course of SpA.…”
Section: Discussionmentioning
confidence: 61%
“…Joint damage in JIA results from synovitis with formation of pannus, which, in the so-called outside-in mechanism, destroys cartilage and bone, leading to subchondral erosions, inflammatory cysts, and ankylosis [6]. A similar inflammatory process, osteitis, starts within the subchondral bone marrow and, through the inside-out mechanism, first leads to subchondral cysts formation, with further evolution to erosions and hyaline cartilage damage [9][10][11]. Another location of disease, typical for the juvenile enthesitisrelated arthritis (ERA) subtype of JIA, are tendons, ligaments, and capsule entheses with inflammation (enthesitis) may lead to bone reaction with the formation of cysts and erosions and peri-entheseal soft tissue involvement [12].…”
Section: Introductionmentioning
confidence: 99%
“…Destructive inflammatory lesions developing in the course of JIA include cysts, erosions, joint space narrowing, chondromalacia, ankylosis, and secondary osteoarthritis. Joint inflammation overlapping natural bone growth in juveniles may lead to growth disturbances and developmental disorders [9,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…According to EULAR 8 , MRI is the gold standard for the diagnosis of juvenile idiopathic arthritis. Through this examination, it is possible to identify synovial effusion and thickening in early stages, and, in more advanced stages, joint pannus, bone erosions, cartilage thinning and deformity of joint surfaces can be identified 10 …”
Section: Introductionmentioning
confidence: 99%
“…Through this examination, it is possible to identify synovial effusion and thickening in early stages, and, in more advanced stages, joint pannus, bone erosions, cartilage thinning and deformity of joint surfaces can be identified. 10 The temporomandibular joint (TMJ) has been called in the literature the "forgotten joint". 11 Diagnosing TMJ arthritis is challenging as clinical signs are uncharacteristic and disease onset is usually asymptomatic.…”
mentioning
confidence: 99%